Analysis of Gross Up and Net Method in Tax Planning Order Study Case in PT. Sumber Citra Megah - Christian, Tommy; Hardan, Ahmaf Omar Nafi (Yayasan Sinergi Kawula Muda, 2023)
A tax management system for the effective is the most important thing to stay in a current situation. There needs to be a tax planning in the work plan without having to violate prevailing tax law. Implementation planning income tax article 21 by the company expected to minimize employees tax cost, that will benefit both sides. This research using any objects PT. Sumber Citra Megah. Implementation planning income tax article 21 by the company is expected to to minimize the tax charges to be indebted issued employees, that automatically be able to maximize profit after tax. The result showed that PT. Sumber Citra Megah do not planning income tax article 21 optimally because the calculation of THR, the salary employees and the competitive salary survey. Based on the research, company must evaluate income tax article 21 planning optimally by did not violate tax provisions apply. In this case, the company should provide income tax allowances using the gross up method, and replace the provision of in-kind with allowances in the form of money that flow directly to employees, because that way these costs can increase the company's fiscal costs and on the side of the employees it is also profitable because their take home pay will increase.